Increased Sphingosine-1-Phosphate Serum Concentrations in Subjects with Periodontitis: A Matter of Inflammation - Moritz E; Jedlitschky G; Negnal J; Tzvetkov MV; Daum G; Dörr M; Felix SB; Völzke H; Nauck M; Schwedhelm E; Meisel P; Kocher T; et al. (Dove Medical Press, 2021)
Eileen Moritz,1,2,* Gabriele Jedlitschky,1,* Josefine Negnal,1 Mladen V Tzvetkov,1 Günter Daum,3,4 Marcus Dörr,2,5 Stephan B Felix,2,5 Henry Völzke,2,6 Matthias Nauck,2,7 Edzard Schwedhelm,4,8 Peter Meisel,9 Thomas Kocher,9 Bernhard H Rauch,1,2,10,* Birte Holtfreter9,* 1Institute of Pharmacology, Department of General Pharmacology, University Medicine Greifswald, Greifswald, Germany; 2German Center for Cardiovascular Research (DZHK), Partner Site Greifswald, Greifswald, Germany; 3Clinic and Polyclinic for Vascular Medicine, University Heart Center, University Medical Center Hamburg-Eppendorf, Hamburg, Germany; 4German Center for Cardiovascular Research (DZHK), Partner Site Hamburg/Kiel/Lübeck, Hamburg, Germany; 5Department of Internal Medicine B, University Medicine Greifswald, Greifswald, Germany; 6Institute for Community Medicine, University Medicine Greifswald, Greifswald, Germany; 7Institute of Clinical Chemistry and Laboratory Medicine, University Medicine Greifswald, Greifswald, Germany; 8Institute of Clinical Pharmacology and Toxicology, University Medical Center Hamburg-Eppendorf, Humburg, Germany; 9Dental Clinics, Department of Periodontology, University Medicine Greifswald, Greifswald, Germany; 10Carl von Ossietzky Universität Oldenburg, Department of Human Medicine, Section of Pharmacology and Toxicology, Oldenburg, Germany*These authors contributed equally to this workCorrespondence: Bernhard H RauchCarl von Ossietzky Universität Oldenburg, Department of Human Medicine, Section of Pharmacology and Toxicology, Carl-von-Ossietzky-Str. 9-11, Oldenburg, 26129, GermanyTel +49 (0) 441 798 4930Fax +49 (0) 441 798 3088Email Bernhard.Rauch@uni-oldenburg.dePurpose: Periodontitis is an inflammatory disease of the oral cavity with an alarmingly high prevalence within the adult population. The signaling lipid sphingosine-1-phosphate (S1P) plays a crucial role in inflammatory and immunomodulatory responses. In addition to cardiovascular disease, sepsis and tumor entities, S1P has been recently identified as both mediator and biomarker in osteoporosis. We hypothesized that S1P may play a role in periodontitis as an inflammation-prone bone destructive disorder. The goal of our study was to evaluate associations between periodontitis and S1P serum concentrations in the Study of Health in Pomerania (SHIP)-Trend cohort. In addition, we investigated the expression of S1P metabolizing enzymes in inflamed gingival tissue.Patients and Methods: We analyzed data from 3371 participants (51.6% women) of the SHIP-Trend cohort. Periodontal parameters and baseline characteristics were assessed. Serum S1P was measured by liquid chromatography tandem mass spectrometry. The expression of S1P metabolizing enzymes was determined by immunofluorescence staining of human gingival tissue.Results: S1P serum concentrations were significantly increased in subjects with both moderate and severe periodontitis, assessed as probing depth and clinical attachment loss. In contrast, no significant association of S1P was seen with caries variables (number and percentage of decayed or filled surfaces). S1P concentrations significantly increased with increasing high-sensitivity C-reactive protein (hs-CRP) levels. Interestingly, inflamed compared to normal human gingival tissue exhibited elevated expression levels of the S1P-generating enzyme sphingosine kinase 1 (SphK1).Conclusion: We report an intriguingly significant association of various periodontal parameters with serum levels of the inflammatory lipid mediator S1P. Our data point towards a key role of S1P during periodontitis pathology. Modulation of local S1P levels or its signaling properties may represent a potential future therapeutic strategy to prevent or to retard periodontitis progression and possibly reduce periodontitis-related tooth loss.Keywords: sphingosine-1-phosphate, lipid mediator, periodontitis, inflammation